2021
DOI: 10.3390/antibiotics10080919
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Topical Administration of Drugs and Biological Active Substances for Dental Implants—A Narrative Review

Abstract: Dental implants are, nowadays, established surgical devices for the restoration of lost teeth. Considered as an alternative for traditional prosthetic appliances, dental implants surpass them in reliability and patient feedback. Local drug delivery around the implants promotes osseointegration and reduces peri-implantitis. However, there are currently no methods of a multiple, precise topical administration of drugs to the implant area. Engineering coatings on the implants, drug application on carriers during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…The system could mitigate the effects of the above factors and achieve ideal osseointegration by releasing different drugs around Ti implants. For example, the release of anti-bone resorption drugs could transform bone metabolism into bone deposition by inhibiting the absorptive activity of osteoclasts [ 190 , 191 ]. Additionally, with the release of anti-inflammatory drugs, the system could solve aseptic loosening by mitigating local inflammatory responses [ 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…The system could mitigate the effects of the above factors and achieve ideal osseointegration by releasing different drugs around Ti implants. For example, the release of anti-bone resorption drugs could transform bone metabolism into bone deposition by inhibiting the absorptive activity of osteoclasts [ 190 , 191 ]. Additionally, with the release of anti-inflammatory drugs, the system could solve aseptic loosening by mitigating local inflammatory responses [ 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pore size of the manufactured Van/SBA-15/CS-GP-SA was larger than the other two groups (Figure 5). This indicates that the addition of Van/SBA-15 to CS-GP-SA has a significant influence on the surface structure (Jaidev and Chatterjee, 2019;Ouyang et al, 2019;Metwally et al, 2020;Wychowański et al, 2021).…”
Section: Characteristics Of Van/sba-15/ Cs-gp-samentioning
confidence: 97%
“…Therefore, antimicrobial drug carriers, a topical strategy, have become an adjunct to the prevention and treatment of infections in jaw defects ( Alazzawi et al, 2021 ; Han et al, 2021 ). Topical administration at or near the site of infection diminishes the toxic effects of antibacterial agents, reduces the required dose of antibiotics, and enhances the bioavailability and safety of the drug ( Wychowański et al, 2021 ; Zheng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic antibiotic applications have drawbacks such as systemic toxicity [75], low bioavailability, and antibiotic resistance [74,76,77], making local antibiotic treatment a preferred method of drug administration [76]. Studies have shown many potential benefits from localized drug delivery for peri-implantitis [77][78][79].…”
Section: Insect-inspired Patternsmentioning
confidence: 99%
“…Apart from their potential to serve as efficient drug delivery platforms, CNMs are also established antibacterial agents, most commonly via contact-mediated biocidal action [76]. The bacterial cell wall permeability is altered by the nanoparticles that are positively charged, which electrostatically attract the negatively charged bacterial cell membrane, resulting in its rupture, followed by leakage of intracellular organelles.…”
Section: Antibacterial Propertymentioning
confidence: 99%